2005
DOI: 10.1038/nature03451
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of entomopathogenic nematodes by insect-damaged maize roots

Abstract: Plants under attack by arthropod herbivores often emit volatile compounds from their leaves that attract natural enemies of the herbivores. Here we report the first identification of an insect-induced belowground plant signal, (E )-b-caryophyllene, which strongly attracts an entomopathogenic nematode. Maize roots release this sesquiterpene in response to feeding by larvae of the beetle Diabrotica virgifera virgifera, a maize pest that is currently invading Europe. Most North American maize lines do not release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
1,086
5
26

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,128 publications
(1,134 citation statements)
references
References 34 publications
17
1,086
5
26
Order By: Relevance
“…Indirect defenses are widespread and include domatia, extrafloral nectar, and food bodies which provide shelter and nutrition for predators and parasitoids, as well as herbivory-induced plant volatiles (HIPVs) which convey information about feeding herbivores (Heil, 2008). Field studies with the native tobacco Nicotiana attenuata , a desert annual, and with maize have shown that HIPVs can reduce herbivore loads by 24% to more than 90%, by increasing both predation and parasitization of herbivores (Kessler and Baldwin, 2001; Rasmann et al, 2005; Halitschke et al, 2008; Degenhardt et al, 2009; Allmann and Baldwin, 2010) and deterring herbivore oviposition (Kessler and Baldwin, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect defenses are widespread and include domatia, extrafloral nectar, and food bodies which provide shelter and nutrition for predators and parasitoids, as well as herbivory-induced plant volatiles (HIPVs) which convey information about feeding herbivores (Heil, 2008). Field studies with the native tobacco Nicotiana attenuata , a desert annual, and with maize have shown that HIPVs can reduce herbivore loads by 24% to more than 90%, by increasing both predation and parasitization of herbivores (Kessler and Baldwin, 2001; Rasmann et al, 2005; Halitschke et al, 2008; Degenhardt et al, 2009; Allmann and Baldwin, 2010) and deterring herbivore oviposition (Kessler and Baldwin, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…But because HIPVs can be perceived by many other members of the ecological community—from herbivores, pollinators, predators and parasitoids to competing or parasitic plants—it is not clear whether HIPVs increase plant fitness in nature (Dicke and Baldwin, 2010; Kessler and Heil, 2011). The field studies described above have either spanned too short a time to reveal Darwinian fitness benefits, or have not reported fitness data at all (Kessler and Baldwin, 2001; Rasmann et al, 2005; Halitschke et al, 2008; Degenhardt et al, 2009; Allmann and Baldwin, 2010). Two laboratory studies showed that parasitization of herbivores can increase plant reproduction (van Loon et al, 2000; Hoballah and Turlings, 2001), but the parasitization in these studies was not mediated by HIPVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis has been shown to emit two terpenoids, (3,S)-(E)-nerolidol and its derivative (E)-4,8-dimethyl-1,3,7-nonatriene, when the strawberry nerolidol synthase gene was introduced into the plants, resulting in greater attraction of the predators of predatory mites (Kappers et al 2005). Caryophyllene, emitted from the roots of Maize plants, is known to be an herbivore-induced below-ground signal, which strongly attracts entomopathogenic nematodes (Rasmann et al 2005;Delory et al 2016). Similarly, Ozawa et al (2000) demonstrated that (Lotus japonicus) shoots infested with spider mites released a blend of volatiles that attracted predators of mites (Phytoseiulus persimilis).…”
Section: Terpenoid Volatiles: An Immediate Response In Plant Defensementioning
confidence: 99%
“…Although terpenes are mostly studied in the above-ground tissues, recently, their novel function in the below-ground environment, as signaling molecules, has been identified (Karban et al 2014;Delory et al 2016). For example, β-caryophyllene, released from the roots of maize plants against beetle (Diabrotica virgifera) attack, acts as a volatile signal to attract predatory nematodes, which will defend plants indirectly from further damage (Rasmann et al 2005). Similarly, the Hedychium coronarium farnesyl pyrophosphate synthase gene shows a quick response to herbivory and wounding and is involved in floral biosynthesis (Lan et al 2013).…”
Section: Introductionmentioning
confidence: 99%